PENGARUH METODE PROYEK ECOBRICK TERHADAP KEMAMPUAN KERJASAMA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK NUR ILAAHI LUBUK BUAYA PADANG - Rahmi Andre Yelfi Yusuf; Serli Marlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The goal of this research is to determine how the ecobrick project approach affects the collaboration abilities of the kindergarten students at Nur Ilaahi Lubuk Buaya. Preliminary observations revealed that the kids' cooperation skills were still not fully developed. Despite being expected to work in groups, the kids continued to work alone. This research employs a quasi-experimental technique and a quantitative approach. All 74 students of Nur Ilaahi Lubuk Buaya Padang Kindergarten, split up into 5 classes (B1 through B5), make up the study's population. With 15 kids from each class—class B1 being the experimental class and class B3 being the control class—a sample of 30 kids was chosen. Cluster sampling was the method of sampling that was used. Tests, documentation, and observation were among the methods used to gather data. Among the data analysis methods were hypothesis testing, homogeneity testing, and normality testing. With a Sig. (2-tailed) value of 0.000, which is less than 0.05, the study's results revealed that the experimental class's average pre-test score was 8.13 and rose to 18.2 in the post-test. This suggests that the cooperative abilities of the 5–6-year-old students at Nur Ilaahi Lubuk Buaya Padang Kindergarten are impacted by the ecobrick project technique.